Synthesis of titanium-nickel shape memory alloy via electrodeposition route - De Guzman, Yvette Marie M. (2010)
TiNi shape memory alloys (SMAs) have been widely used in the fields of engineering and medicine due to their unique shape memory effect and super-elasticity, which are displayed during martensitic transformations. However, the fabrication process of TiNi SMA is very expensive. In this study, the feasibility of synthesizing a TiNi alloy which exhibits shape memory behavior using a much cheaper and less complicated method via electrodeposition of nickel on titanium substrate followed by successive heat treatment in a tube furnace was investigated. Plating was carriad out using a typical Watts bath formulation to deposit the desired weight percent of nickel. Furnace annealing of the plated strips to achieve thermal alloying was performed for different time durations over the temperature tange of 500°C to 1000°C. Annealed samples after quenching were subjected to shape memory tests using different heating rates. All samples exhibited shape memory effect (SME) and the sample annealed at 600°C manifested very strong SME with a highest percent recovery of 92.23%. DSC analysis on the annealed samples showed austenite transformation temperatures close to 100°C. XRD analysis showed TiNi-B2 TiNi-B19' diffraction peaks on all annealed samples. SEM/BSE analysis showed planar growth of intermetallic layers and as the annealing temperature is increased, the layers become thicker. The formation of the total intermetallic layer appears to obey very well the empirical Arrhenius type of kinetics equation reported in literarute for intermetallic systems and the activation for the growth of the total intermetallic layer at one side of the strip was calculated to be 138.47 kJ/mol, which is within the range of activation energies for TiNi that is published in literature.